Analisis Kesulitan Membaca Permulaan Siswa Kelas II SDN 5 Praya Tahun 2021/2022 - Hartini, Baiq Handayani Dwi; Intiana, Siti Rohana Hariana; Jaelani, Abdul Kadir (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Analysis of Student reading difficulties for grade II students of SDN 5 Praya for academic year 2021/2022. The aims of this study were 1) to analyze the various difficulties in early reading experienced by the second grade students of SDN 5 Praya 2) to describe the factors that hindered the students early reading difficulty, and 3) to find out the solutions the teacher in overcoming the students early reading difficulty. This study uses a qualitative approach and the type of descriptive research. The research was conducted at SDN 5 Praya in the odd semester 2021/2022 academic year. The primary data sources in this study were the results of interviews while the secondary data in this study were in the form of books, notes, data about schools, learning documents, as well as documentation results such as: photos, videos, and recordings related to students' reading activities. Informants in this study were grade II students, second grade homeroom teachers and the Principal of SDN 5 Praya. Data collection techniques were carried out by means of observation, interviews and documentation. The data analysis technique used in this research is done by compiling the data obtained from the results of interviews, field notes, and documentation systematically. The results of this study are 1) the difficulties of students in reading early in class II at SDN 5 Praya 2021/2022, namely: students do not recognize letters, have difficulty distinguishing letters, students cannot read words, omit letters, have difficulty reading punctuation marks, and have difficulty recognizing word meanings. 2) The factors that hinder students in having difficulty reading early, a) lack of interest in student learning, b) students do not attend Kindergarten, and c) families do not support. 3) The solutions applied by the teacher to overcome the problems of Students with Beginning Reading Difficulties; a) the teacher provides additional hours for students who still have difficulty reading the beginning, b) the teacher gives more and special attention to students who still cannot read the beginning, c) the letters are used as singing material, and 4) displays the letters and discusses the shape (characteristics) in particular. Letters that have similar shapes (eg p, b, and d ).